The Effect and Optimal Parameters of Repetitive Transcranial Magnetic Stimulation on Poststroke Dysphagia: A Meta-Analysis of Randomized Controlled Trials - Qiao, Jia; Ye, Qiu-ping; Wu, Zhi-min; Dai, Yong; Dou, Zu-lin (Frontiers in Neuroscience, 2022)
Objective: To evaluate the efficacy of repetitive transcranial magnetic stimulation (rTMS) treatment for post-stroke dysphagia (PSD) and explore the optimal stimulation parameters. Method: The database of Medline, Embase, Web of Science, and Cochrane Library were searched from the establishment to June 2021. All randomized controlled trials about rTMS for PSD were enrolled. Dysphagia Grade (DG) and Penetration Aspiration Scale (PAS) were applied as the major dysphagia severity rating scales to evaluate the outcomes. Results: A total of 12 clinical randomized controlled studies were included in this meta-analysis. The summary effect size indicated that rTMS had a positive effect on PSD (SMD=-0.67, p<0.001). The subgroup analysis for treatment duration and different stroke stages showed significant differences (treatment duration >5 days: SMD=-0.80, p<0.001; subacute phase: SMD=-0.60, p<0.001). Furthermore, no significant differences were observed among the other stimulation parameters subgroups (including stimulation frequency, location, and single stimulation period) (p>0.05). Conclusion: rTMS is beneficial to the recovery of PSD patients, while an intervention of more than five days and in the subacute phase might bring new strategies and rational therapeutics to the management of PSD.